2019
DOI: 10.3390/pr7080491
|View full text |Cite
|
Sign up to set email alerts
|

Flow Behavior and Hot Processing Map of GH4698 for Isothermal Compression Process

Abstract: An in-depth understanding of the flow behaviors of materials deformed at high temperatures is of paramount significance. However, insufficient research on the nickel-based GH4698 alloy has resulted in inaccurate material flow prediction or even cracking in the practical billet opening of GH4698 large forgings. In this study, hot compressions were performed at 950–1150 °C and 0.001–3 s−1. Single-peaked strain-stress curves were obtained under various conditions, owing to dislocation motions in dynamic recrystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Under a high temperature and a low strain rate, the true stress was low due to a low dislocation motion barrier. This phenomenon was also found in the compression of 300M steel [ 11 ], GH4169 alloy [ 17 ], GH4698 alloy [ 18 ], etc. The previous result in Figure 3 , that the ultimate elongation was greater under a higher strain rate and a lower temperature, could be interpreted by the flow stress curves in Figure 5 .…”
Section: Resultsmentioning
confidence: 72%
“…Under a high temperature and a low strain rate, the true stress was low due to a low dislocation motion barrier. This phenomenon was also found in the compression of 300M steel [ 11 ], GH4169 alloy [ 17 ], GH4698 alloy [ 18 ], etc. The previous result in Figure 3 , that the ultimate elongation was greater under a higher strain rate and a lower temperature, could be interpreted by the flow stress curves in Figure 5 .…”
Section: Resultsmentioning
confidence: 72%
“…Chen et al [39] found that the hot working ability of a nickel-based GH4698 alloy markedly decreased under lower temperatures and higher strain rates in isothermal compressions: this alloy is extremely sensitive to thermal processing parameters and cracking may easily occur. An Arrhenius model was used to estimate the flow stresses and profiles for processing under various thermal conditions.…”
Section: Rollingmentioning
confidence: 99%
“…Yao et al [42] created the processing maps of the GH909 superalloy. Chen et al [43] constructed a processing map of GH4698 alloy at high-temperature deformation conditions. Jaladurgam and Kanjarla [44] developed a processing map to predict the safe hot workability window of Hastelloy C-276 alloy.…”
Section: Introductionmentioning
confidence: 99%